Philosophical Underpinnings of Benedict XVI’s Notion of Development - Ozioko, Johnson Uchenna (Alpha Omega, 2017)
Summary: Beyond the evident theological appeal of Benedict XVI’s Caritas in veritate dedicated to integral human development, this social encyclical is also impregnated with very rich and deep, philosophical significance. This article systematically investigates the philosophical foundations of Benedict’s perspective on the question of development. Beginning from an appraisal and enunciation of the solid theistic-anthropological grounding of the encyclical, it explores key philosophical elements which undergird Benedict’s notion of development and which combine to render his encyclical not only theologically orthodox and refreshing but also philosophically cogent and persuasive. Key Words: Benedict XVI, human development, charity, truth, justice, ethics, faith, reason, theistic anthropology, transcendence. Parole chiave: Benedetto XVI, sviluppo umano, carità, verità, giustizia, etica, fede, ragione, antropologia teistica, trascendenza.